Feeling at home in nature: a mixed method study of the impact of visitor activities and preferences in a prison visiting room garden. Issue 4 (18th May 2020) - Toews, Barb; Wagenfeld, Amy; Stevens, Julie; Shoemaker, Carissa
Abstract: More than 5 million children will experience parental incarceration at some point in their lives, an adverse childhood event that will impact their relationship with their parents and the trajectory of their lives. Parent-child visits in supportive child-friendly visiting environments can benefit both the child and parent and mitigate negative future effects. Outdoor gardens and play spaces may provide such a visiting environment. This mixed method study explored the activities and uses of a visitor's garden in a women's state prison and the perceived impact on the visit. Results find that child and family activities included physical and creative play and nature engagement. Ninety percent of garden visitors indicated the garden improved their visits and identified the following as related to that impact: more child-friendly environment, improved affective experience, home-like visiting environment, and more and better parent-child interactions. Implications for incarcerated parents and children as well as future research are discussed.